Resveratrol-Mediated Gold-Nanoceria Synthesis as Green Nanomedicine for Phytotherapy of Hepatocellular Carcinoma - Adel Ghorani-Azam; Javad Mottaghipisheh; Mohammad Sadegh Amiri; Mohammad Mashreghi; Alireza Hashemzadeh; Aliakbar Haddad-Mashadrizeh; Fahimeh Nourbakhsh; Mohabat Nadaf; Mohsen Qayoomian; Mohammad Ehsan Taghavizadeh Yazdi; Sara Vitalini; Marcello Iriti (Frontiers in Bioscience-Landmark, 2022)
Background: In the present study, resveratrol was used to prepare complexes of cerium and nanoceria, also coated with gold (CeO2@Au core-shells) to improve the surface interactions in physiological conditions. Methods: The CeO2@Au core-shells were characterized using powder X-ray diffraction (PXRD), Fourier transforms infrared spectroscopy (FTIR), transmission electron microscope (TEM) analysis, dynamic light scattering (DLS) and ζ potential. Results: The experiment was led to the successful synthesis of nanosized CeO2@Au core-shells, although agglomeration of particles caused the distribution of the larger particles. The TEM analysis demonstrated the particles sizes ranged from 20 nm to 170 nm. Moreover, the PXRD analysis showed that both nanoceria and gold with the same crystal systems and space groups. To investigate the anticancer activity of the CeO2@Au core-shells, the cytotoxicity of the nanoparticles was investigated against liver cancerous cell lines (HepG2). Conclusions: The results indicated biosynthesized NCs have significant cellular toxicity properties against HepG2 and could be utilized in hepatocarcinoma therapy. Further in vivo investigations is proposed to be designed to assess anti-cancer and safety effects of fabricated nanocomposites.